DEVELOPMENT AND VALIDATION OF UV SPECTROPHOTOMETRIC METHODS FOR DETERMINATION OF MEGLUMINE IN BULK - V. U., Barge; P. B., Jadhav; S. R., Attarde; K. V., Kodre; R. Y, Patil (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
UV, first, second and third derivative spectrophotometric methods have been developed for the determination of meglumine. The solutions of standard and sample were prepared in distilled water. For the first method i.e. calibration curve UV spectrophotometric method, the quantitative determination of the drug was carried at 254 nm and the linearity range was found to be 10 – 60 µg/ml. For the first, second, third derivative spectrophotometric methods the drug was determined at 247 nm, 216 nm, 266 nm with the linearity range 10 – 60 µg /ml. The calibration graphs constructed at their wavelength of determination were found to be linear for UV and derivative spectrophotometric methods. All the proposed methods have been extensively validated. There was no significant difference between the performance of the proposed methods regarding the mean values and standard deviations.